Single-phase convective heat transfer in a cold plate with wavy channels - Low, Jing Peng (Nanyang Technological University, 2020)
As the electronics and computing technologies advances, the amount of heat flux generated by these devices also increases. Therefore, the demand for efficient heat removing has been ever increasing. The microchannel heat sink provides superior heat transfer capabilities and it had been studied for a few decades to even further enhance the heat transfer. In this project, two designs with different channel configurations were implemented to compare the heat transfer and hydrodynamic performance to determine which configurations is the best design in removing heat. The heat sink designs are microchannel and microgap. The microchannel configurations include straight channel, serpentine channel and single-walled wavy channel. For the microgap study, the configurations include parallel gap, wavy parallel gap, top wall wavy gap and bottom wall wavy gap. The numerical simulations were conducted with the flowrates ranging from 1.67 x 10-6 m³/s to 1.503 x 10-5 m³/s for the microchannel and pressure drops ranging from 717 Pa to 7856 Pa for the microgap. The results of the simulation showed that the introduction of waviness on microchannel and microgap enhanced the heat transfer performance. The highest heat transfer coefficient recorded was 129.38 kW/m²·K with the single-walled wavy microchannel. The serpentine channel also has better thermal performance than the straight channel but not as efficient as the single-walled wavy channel. However, having a high heat transfer coefficient causes a pressure drop of 9.67 times higher than the straight channel. The waviness introduction on microgap had similar results as the microchannel. The bottom wall wavy microgap also recorded the highest heat transfer coefficient of 20.625 kW/m²·K at the pressure drop of 7856 Pa, that is 18.6 percent higher than the parallel microgap. The wavy parallel migrogap has a 2.89 percent higher and the top wall wavy microgap has a 7.99 percent higher as compared to the parallel microgap. Therefore, for both microgeometries, the single walled wavy channel and bottom wall wavy gap achieved the best thermal performance among all design configurations.